Subcutaneous axillary primary epithelioid hemangioendothelioma: report of a rare case - Takayoshi Niwa; Takaaki Konishi; Asako Sasahara; Ayaka Sato; Arisa Morizono; Mayumi Harada; Kotoe Nishioka; Osamu Fukuoka; Naohiro Makise; Yuki Saito; Mizuo Ando; Takako Yoshimoto; et al. (Surgical Case Reports, 2022)
Abstract Background Epithelioid hemangioendothelioma (EHE) is a rare and slow-growing malignant vascular neoplasm composed of epithelioid endothelial cells within a distinctive myxohyaline stroma. It most commonly involves somatic soft tissue, lungs, liver and bone. Herein, we describe a case of EHE arising in the axillary region. Case presentation A 61-year-old man was under observation for multiple hepatic hemangiomas. Fluorodeoxyglucose–positron emission tomography/computed tomography showed specific uptake in a right axillary tumor. The patient was referred to our department for further investigation of the axillary tumor. An elastic-soft and poorly mobile tumor was palpable in the right axilla. Contrast-enhanced computed tomography showed a right axillary tumor and enlarged hepatic hemangiomas. In addition, multiple nodules in both lungs, a left renal angiomyolipoma, and left adrenal adenoma were revealed. Ultrasonography showed masses in both lobes of the thyroid gland, and a 30-mm lobulated hypoechoic mass in the axilla with well-defined and rough borders, showing internal heterogeneity. Fine-needle aspiration cytology was performed on the thyroid and axillary tumors: the thyroid tumor was class V, raising suspicion of papillary thyroid cancer (PTC); the left superior internal jugular node was class V, raising suspicion of metastasis of PTC; and the axillary tumor was class III, raising suspicion of a mesenchymal tumor with few epithelioid cells. The multiple lung nodules were diagnosed as metastatic tumors derived from thyroid cancer. We diagnosed these diseases as PTC of T1b(m)N1bM1(lung) Stage IVB and a right axillary tumor of unclear origin. However, it was assumed to be a primary mesenchymal tumor or a lymph node metastasis from lung cancer or occult breast cancer. We performed total thyroidectomy, left cervical lymph node dissection, and right axillary tumor excision. Histopathologic examination revealed the thyroid tumor as a PTC and the axillary tumor as an EHE. The EHE showed nuclear atypia, necrosis and high mitotic figures. Hence, it was considered to be a high-risk EHE. Conclusions We experienced a rare primary subcutaneous axillary EHE with metastatic thyroid cancer in the lung. Since our case was classified as a high-risk EHE, a close follow-up would be appropriate.